Induction of Labour by Extra-Amniotic Saline infusion in Women having Previous One Cesarean Section - SajidaAsghar,SaniyaNaheed,Dureshahwara,AnitaRoshan,MumtazJahan,TahiraNasreen,Nazia, SajidaAsghar,SaniyaNaheed,Dureshahwara,AnitaRoshan,MumtazJahan,TahiraNasreen,Nazia (Journal of Rawalpindi Medical College, 2019)
Background: To determine the efficacy of labor induction by extra-amniotic saline infusion in women having previous one lower segment cesarean section. Method: All women, fulfilling inclusion criteria, were selected for study. In lithotomy position, Foley’s catheter no.16 was passed in the cervical canal extra amniotically and 30 ml sterile water was injected to inflate the balloon. Then 0.9 % normal saline at 40 ml/hour injected into the extra-amniotic space. Results: The successful cervical ripening was 74.8% (49/66). The number of women delivered vaginally within 24 hours of insertion of Foley’s catheter were 56.1% (37/66). The rate of uterine rupture was 1.5% (1/66). Thus extra-amniotic saline infusion through trans-cervical was an effective method for induction of labour in women having previous one lower segment cesarean section was 56.1% (37/66). Conclusion: Extra-amniotic saline infusion is an effective method for labor induction in women having previous one lower segment cesarean section. Keywords: Induction, labour, caesarean section, extra-amniotic saline infusion, Bishop score etc.